2018
DOI: 10.1007/s12224-018-9313-8
|View full text |Cite
|
Sign up to set email alerts
|

Naturally recruited herbaceous vegetation in abandoned Belgian limestone quarries: towards habitats of conservation interest analogues?

Abstract: We examined if naturally recruited herbaceous vegetation in abandoned Belgian limestone quarries tend towards plant communities analogous to semi-natural habitats of conservation interest. We studied taxon-based assemblages (using two-dimensional non-metric multidimensional scaling ordination) and functional patterns (relative to Grime's competitor, stress tolerator and ruderal plant strategies (CSR) classification) of plant communities (n = 360 plots) among three different time periods after quarry abandonmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Critically endangered species, which are the most valuable from a conservation perspective, occupied sparsely vegetated habitats with still exposed bedrock as documented by Gilardelli et al (). This observation agrees with other biodiversity surveys of various groups of organisms in post‐mining sites, which revealed that such biotopes are often highly heterogeneous, containing diverse abiotic conditions, and thus harboring a high number of species (Beneš et al ; Bétard ; Pitz et al ). These cannot be achieved in the recent cultural landscape or even in traditionally protected areas where barren land and diverse successional stages are often lacking (Jarošik et al ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Critically endangered species, which are the most valuable from a conservation perspective, occupied sparsely vegetated habitats with still exposed bedrock as documented by Gilardelli et al (). This observation agrees with other biodiversity surveys of various groups of organisms in post‐mining sites, which revealed that such biotopes are often highly heterogeneous, containing diverse abiotic conditions, and thus harboring a high number of species (Beneš et al ; Bétard ; Pitz et al ). These cannot be achieved in the recent cultural landscape or even in traditionally protected areas where barren land and diverse successional stages are often lacking (Jarošik et al ).…”
Section: Discussionsupporting
confidence: 91%
“…It is useful to identify the conservation potential of particular successional stages which would provide optimal conditions for the establishment of species compositions that are analogous to rare natural habitats (Pitz et al ). Participation of threatened categories increased with ongoing succession except for the most valuable critically endangered species, which tended not to establish in habitats with continuous cover.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposal may be enlarged by adding several bioclimatically and biogeographically differentiated subtypes. The same new habitat might also include abandoned quarries, a similar context where communities of conservation in-terest were already depicted in several European countries (e.g., Mota et al 2004;Gentili et al 2011;Pitz et al 2018). Also 'Mediterranean heaths' , due to their peculiar and diversified composition, deserve in our opinion the inclusion in the HD as a new habitat with four different subtypes, defined according to their different soil and wetness conditions.…”
Section: Discussionmentioning
confidence: 71%
“…To allow quarry activities, authorities generally require planning details to ensure the subsequent restoration. Adaptive management of quarries could increase biodiversity and vegetation of high conservation value in industrialized and farmed landscapes [ 20 , 21 , 22 ], and quarry rehabilitation could represent an opportunity to re-establish native grassland species [ 23 , 24 ]. In limestone quarries, restoration ecologists need to develop adequate procedures for establishing native plant communities and the success will depend on improving the substrate condition, selecting efficient species pool for revegetation and preventing invasion by alien species [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%